Intragenic complementation of herpes simplex virus ICP8 DNA-binding protein mutants. - Gao, M (1993)
The major DNA-binding protein, or infected-cell protein 8 (ICP8), of herpes simplex virus is required for viral DNA synthesis and normal regulation of viral gene expression. Previous genetic analysis has indicated that the carboxyl-terminal 28 residues are the only portion of ICP8 capable of acting independently as a nuclear localization signal. In this study, we constructed a mutant virus (n11SV) in which the carboxyl-terminal 28 residues of ICP8 were replaced by the simian virus 40 large-T-antigen nuclear localization signal. The n11SV ICP8 localized into the nucleus and bound to single-stranded DNA in vitro as tightly as wild-type ICP8 did but was defective for viral DNA synthesis and viral growth in Vero cells. Two mutant ICP8 proteins (TL4 and TL5) containing amino-terminal alterations could complement the n11SV mutant but not ICP8 gene deletion mutants. Cell lines expressing TL4 and TL5 ICP8 were isolated, and in these cells, complementation of n11SV was observed at the levels of both viral DNA replication and viral growth. Therefore, complementation between n11SV ICP8 and TL4 or TL5 ICP8 reconstituted wild-type ICP8 functions. Our results demonstrate that (i) the carboxyl-terminal 28 residues of ICP8 are required for a function(s) involved in viral DNA replication, (ii) this function can be supplied in trans by another mutant ICP8, and (iii) ICP8 has multiple domains possessing different functions, and at least some of these functions can complement in trans.